Scenarios and the art of worldmaking - Vervoort, Joost M.; Bendor, Roy; Kelliher, Aisling; Strik, Oscar; Helfgott, Ariella E.R. (Futures : the journal of policy, planning and futures studies, 2015)
•We propose worldmaking as a framework for scenario practice.•Worldmaking extends pluralism into ontological domains.•Worldmaking makes contrasts between present/future worlds productive.•Embodied scenario worldmaking empowers the imagination.•We operationalize scenario worldmaking through questions. In this exploratory paper we propose ‘worldmaking’ as a framework for pluralistic, imaginative scenario development. Our points of departure are the need in scenario practice to embrace uncertainty, discomfort and knowledge gaps, and the connected need to capture and make productive fundamental plurality among understandings of the future. To help respond to these needs, we introduce what Nelson Goodman calls worldmaking. It holds that there is no singular, objective world (or “real reality”), and instead that worlds are multiple, constructed through creative processes instead of given, and always in the process of becoming. We then explore how worldmaking can operationalise discordant pluralism in scenario practice by allowing participants to approach not only the future but also the present in a constructivist and pluralistic fashion; and by extending pluralism to ontological domains. Building on this, we investigate how scenario worldmaking could lead to more imaginative scenarios: worldmaking is framed as a fully creative process which gives participants ontological agency, and it helps make contrasts, tensions and complementarities between worlds productive. We go on to propose questions that can be used to operationalize scenario worldmaking, and conclude with the expected potential and limitations the approach, as well as suggestions for practical experimentation.